Distribution and mass of diffuse and dense co gas in the milky way - Roman-Duval, Julia; Heyer, Mark; Brunt, Christopher M.; Clark, Paul; Klessen, Ralf S.; Shetty, Rahul (The astrophysical journal, 2016)
Emission from carbon monoxide (CO) is ubiquitously used as a tracer of dense star-forming molecular clouds. There is, however, growing evidence that a significant fraction of CO emission originates from diffuse molecular gas. Quantifying the contribution of diffuse CO-emitting gas is vital for understanding the relation between molecular gas and star formation. We examine the Galactic distribution of two CO-emitting gas components, a high column density component detected in 13CO and 12CO, and a low column density component detected in 12CO, but not in 13CO. The “diffuse” and “dense” components are identified using a combination of smoothing, masking, and erosion/dilation procedures, making use of three large-scale 12CO and 13CO surveys of the inner and outer Milky Way. The diffuse component, which globally represents 25% (1.5 × 108M⊙) of the total molecular gas mass (6.5 M⊙), is more extended perpendicular to the Galactic plane. The fraction of diffuse gas increases from ∼10%-20% at a galactocentric radius of 3-4 kpc to 50% at 15 kpc, and increases with decreasing surface density. In the inner Galaxy, a yet denser component traced by CS emission represents 14% of the total molecular gas mass traced by 12CO emission. Only 14% of the molecular gas mass traced by 12CO emission is identified as part of molecular clouds in 13CO surveys by cloud identification algorithms. This study indicates that CO emission not only traces star-forming clouds, but also a significant diffuse molecular ISM component.
Gesehen am 04.05.2020